2001
DOI: 10.1034/j.1399-302x.2001.160601.x
|View full text |Cite
|
Sign up to set email alerts
|

A possible mechanism of maxillofacial abscess formation: involvement of Porphyromonas endodontalis lipopolysaccharide via the expression of inflammatory cytokines

Abstract: In a previous study, we developed a specific monoclonal antibody against Porphyromonas endodontalis lipopolysaccharide, and demonstrated that this lipopolysaccharide was detected in bacterially infected root canal fluid. We suggest here that P. endodontalis lipopolysaccharide in the infectious materials plays a stimulatory role in maxillofacial abscess formation via the expression of inflammatory cytokines. Our epidemiological study showed that this lipopolysaccharide was detected in significant levels the inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 26 publications
(28 reference statements)
0
19
0
1
Order By: Relevance
“…Endotoxins are the main virulence factor of these bacteria (7) and exert various biological effects that result in the amplification of inflammatory and immune responses (8). Studies suggest that endotoxins are involved in the pathogenesis of pulpal and periapical inflammation (6,(9)(10)(11)(12)(13)(14)(15). A positive correlation between endotoxin concentration in the root canal and the presence of endodontic signs and symptoms has been shown (16).…”
mentioning
confidence: 94%
“…Endotoxins are the main virulence factor of these bacteria (7) and exert various biological effects that result in the amplification of inflammatory and immune responses (8). Studies suggest that endotoxins are involved in the pathogenesis of pulpal and periapical inflammation (6,(9)(10)(11)(12)(13)(14)(15). A positive correlation between endotoxin concentration in the root canal and the presence of endodontic signs and symptoms has been shown (16).…”
mentioning
confidence: 94%
“…When it comes to P. endodontalis, it is less potent than Streptococcus mutans in stimulating mononuclear cells but more effective in directly inducing IL-6 and IL-1expression by osteoblastic cells (4). This might be significant because these characteristics may enable P. endodontalis to escape the immune response mounted by leukocytes but possess the ability to cause bone resorption at the sites of endodontic infection.…”
Section: Discussionmentioning
confidence: 98%
“…Studies have revealed that the content of endotoxin or LPS in infected root canals is higher in teeth with symptomatic apical periodontitis, teeth with periradicular bone destruction, or teeth with persistent exudation than in those without them (11). P. endodontalis LPS has been detected in samples from infected root canals or in the pus samples of acute abscesses of about 90% of the patients tested; it can play an integral role as a potent stimulator of inflammatory cytokines that are involved in the formation of acute abscesses (4).…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Studies have revealed that the content of endotoxin or LPS in infected root canals is higher in teeth with symptomatic apical periodontitis, teeth with periradicular bone destruction, or teeth with persistent exudation than in those without them (32)(33)(34)(35)(36). Murakami et al (37) detected Porphyromonas endodontalis LPS in samples from infected root canals or in the pus samples of acute abscesses of about 90% of the patients tested. They suggested that P. endodontalis LPS can play an integral role as a potent stimulator of inflammatory cytokines that are involved in the formation of acute abscesses (37).…”
Section: Lipopolysaccharide (Lps)mentioning
confidence: 99%